The "bandeirante" in the textbook: between different narratives (1997-2015) (Ágora Journal, 2022)
The objective of this text is to analyze, through the bandeirante theme, which narrative elements constitute the didactic literature. Based on the concepts of Representation by Roger Chartier, Historical Memory by Jacques Le Goff and Discourse by Mikhail Bakhtin we analyze the bandeirante narrative in six didactic collections evaluated by PNLD. We conclude that several narratives about the Bandeirante are present in the book, one linked to a mythical historical memory and the other to a current historiographical analysis. These two perspectives not only differ from each other, but also oppose each other in the didactic narrative.
Keywords: Textbook; "bandeirante"; historical memory